2010
DOI: 10.1002/pro.560
|View full text |Cite
|
Sign up to set email alerts
|

Subunit arrangement in the dodecameric chloroplast small heat shock protein Hsp21

Abstract: Unfolding proteins are prevented from irreversible aggregation by small heat shock proteins (sHsps) through interactions that depend on a dynamic equilibrium between sHsp subunits and sHsp oligomers. A chloroplast-localized sHsp, Hsp21, provides protection to client proteins to increase plant stress resistance. Structural information is lacking concerning the oligomeric conformation of this sHsp. We here present a structure model of Arabidopsis thaliana Hsp21, obtained by homology modeling, single-particle ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…Numerous substrate-binding sites and intra-oligomer interaction sites were mapped on to its N-terminal arm (Ahrman et al 2007). A structure model of Hsp21, from single-particle electron microscopy studies showed that it too existed as a doubledisc dodecamer, albeit with a relative rotation between the two discs, when compared with the wheat Hsp16.9 dodecamer (Lambert et al 2011). Our studies of the tagged and tagless constructs of rice Hsp26.7 confirm that the length of the Nterminal region has a direct bearing on its oligomer assembly and chaperone activity.…”
Section: Hsp267 Chloroplastmentioning
confidence: 56%
“…Numerous substrate-binding sites and intra-oligomer interaction sites were mapped on to its N-terminal arm (Ahrman et al 2007). A structure model of Hsp21, from single-particle electron microscopy studies showed that it too existed as a doubledisc dodecamer, albeit with a relative rotation between the two discs, when compared with the wheat Hsp16.9 dodecamer (Lambert et al 2011). Our studies of the tagged and tagless constructs of rice Hsp26.7 confirm that the length of the Nterminal region has a direct bearing on its oligomer assembly and chaperone activity.…”
Section: Hsp267 Chloroplastmentioning
confidence: 56%
“…The chloroplast-localized sHsp, Hsp21, increases plant resistance to heat stress upon overexpression (Harndahl et al 1999), and we have previously characterized its structure and function (Ahrman et al 2007a, b;Lambert et al 2011a). We found that Hsp21 has an even better chaperone activity compared with human αB-crystallin, the most wellcharacterized sHsp.…”
Section: Introductionmentioning
confidence: 71%
“…This micro-heterogeneity adds an additional level to the quaternary complexity of the sHSPs exchange of HSP26 could only be quantitatively understood by invoking at least two separate dissociation rate constants, consistent with two types of oligomers [83]. Differences were noted between negative-stain EM reconstructions of Arabidopsis thaliana HSP21, in the presence or absence of cross-linker, hinting at the possibility of multiple conformations differing in terms of compactness [96]. A similar observation was also made in a negative-stain EM study of the octahedral HSP16.5 and Archaeoglobus fulgidus HSP20.2 24mers.…”
Section: Shsp Oligomers Can Transition Between Compact and Expanded Fmentioning
confidence: 89%